EVALUASI KEBERLANJUTAN PENGELOLAAN SISTEM PENYEDIAAN AIR MINUM (SPAM) BERBASIS MASYARAKAT DI KABUPATEN MERAUKE - Letsoin, Stella; Rante, Harmonis; Mujiati (Jurnal ELIPS (Ekonomi, Lingkungan, Infrastruktur, Pengembangan Wilayah, dan Sosial Budaya), 2025)
In an effort to support 100% universal access to drinking water services, the Merauke Regency government providescommunity drinking water facilities and infrastructure in almost all areas. However, most of the construction of theDrinking Water Supply System (SPAM) has failed in post-development management because it is not supported by theformation of a management body at the community level and increasing community capacity by conducting trainingto process the SPAM. Therefore, it is necessary to evaluate the sustainability of SPAM management as a supportingfactor for sustainability or continuity to improve the operation and maintenance of facilities from technical,environmental and social aspects. This research aims to evaluate the existing condition of SPAM and analyse theavailability and needs of clean water for sustainable drinking water for the people of Merauke. Therefore, it isnecessary to conduct a study on community-based SPAM management in terms of technical, institutional, financial,social and environmental aspects.